Moving Target Defense Techniques: A Survey. (22nd July 2018) - Lei, Cheng; Zhang, Hong-Qi; Tan, Jing-Lei; Zhang, Yu-Chen; Liu, Xiao-Hu
Abstract : As an active defense technique to change asymmetry in cyberattack-defense confrontation, moving target defense research has become one of the hot spots. In order to gain better understanding of moving target defense, background knowledge and inspiration are expounded at first. Based on it, the concept of moving target defense is analyzed. Secondly, literature analysis method is adopted to explain the design principles and system architecture of moving target defense. In addition, some relevant key techniques are introduced from the aspects of strategy generation, shuffling implementation, and performance evaluation. After that, the applications of moving target defense in different network architectures are illustrated. Finally, existing problems and future trend in this field are elaborated so as to provide a basis for further study.